In Vitro Assay of Platelet Adhesiveness with Washed and Tanned Human Red Cells - Zbinden, G; Tomlin, S (Thrombosis and Haemostasis, 1968)
An in vitro system is described in which adhesion of blood platelets to washed and tannic acid-treated red cells was assayed quantitatively by microscopic observation. ADP, epinephrine and TAME produced a reversible increase in platelet adhesiveness which was antagonized by AMP. With Evans blue, polyanetholsulfonate, phthalanilide NSC 38280, thrombin and heparin at concentrations above 1-4 u/ml the increase was irreversible. The ADP-induced increase in adhesiveness was inhibited by sodium citrate, EDTA, AMP, ATP and N-ethylmaleimide. EDTA, AMP and the SH-blocker N-ethylmaleimide also reduced spontaneous platelet adhesion to red cells. No significant effects were observed with adenosine, phenprocoumon, 5-HT, phthalanilide NSC 57155, various estrogens, progestogens and fatty acids, acetylsalicylic acid and similarly acting agents, hydroxylamine, glucose and KCN. The method may be useful for the screening of thrombogenic and antithrombotic properties of drugs.